Peningkatan aktivitas belajar mata pelajaran Ilmu Pengetahuan Sosial melalui model pembelajaran Talking Chips di kelas I Madrasah Ibtidaiyah - Uci Nurhayati; Nadlir Nadlir; Fina Atifatul Husna; Nina Rohmatul Fauziyah (JINoP (Jurnal Inovasi Pembelajaran), 2022)
This research is based on the fact that social studies learning in class I, MI Bilingual Roudlotul Jannah, Prambon, tends for students to be inactive during learning. So, this impacts learning activities in social studies learning in the classroom that has not been fully implemented properly. This study aimed to increase learning activities through the application of the talk chips model in social studies learning. The research subjects in this study were 32 bilingual students of class 1 MI Roudlotul Jannah Prambon, Sidoarjo. This research is a type of classroom action research that consists of 2 cycles. Data collection techniques used in this study are observation and documentation—data relating to assessing student learning activities. The results of learning mastery are 36%, then increase in the first cycle to 75%, and in the second cycle, there is an increase until the mastery of learning activities reaches 93%. So, it can be concluded that the chip speaking model can improve learning activities.